Mucormycosis (Zygomycosis) in a heart-Kidney trasplant recipient : recovery after posaconazole therapy (2003)
ABSTRACT: We describe the case of a diabetic patient who developed a severe invasive fungal infection due to Rhizopus species postoperatively after a dual heart/kidney transplantation with subsequent intensive immunosuppressive therapy. No improvement was noted with amphotericin B (deoxycholate) therapy, but salvage treatment with the new azole antifungal posaconazole (200 mg orally 4 times daily) resulted in dramatic clinical improvement as early as 1 week after the initiation of therapy that continued through 23 weeks of treatment, with marked clinical, mycological, and radiological improvements and no adverse events.